2017
DOI: 10.1093/icesjms/fsx014
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the life cycle of the pteropod Limacina helicina from a high resolution interannual time series in the temperate North Pacific

Abstract: Limacina helicina is the dominant pelagic gastropod mollusc species in temperate and polar ecosystems, where it contributes significantly to food webs and vertical flux. Currently, considerable uncertainty exists in the interpretation of L. helicina’s life cycle, hindering our understanding of its potential responses to environmental change. Here, we present size-frequency data on L. helicina collected from three consecutive years (2008–2010) in a North Pacific temperate fjord. Two methods of length-frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 49 publications
4
62
0
Order By: Relevance
“…Pteropods are protandric hermaphrodites, meaning they transition from juveniles to mature males to females during ontogeny (Lalli and Wells, 1978). Their lifespans are thought to be between 0.5 and 2 years (Gannefors et al, 2005;Hunt et al, 2008;Kobayashi, 1974;Wang et al, 2017;Wells, 1976a). Isotopic studies have found that pteropods calcify between 50 and 650 m depth (Fabry and Deuser, 1992;Juranek et al, 2003;Keul et al, 2017), suggesting they are exposed to a wide range of water chemistries during their diurnal migration.…”
Section: Understanding Natural Pteropod Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Pteropods are protandric hermaphrodites, meaning they transition from juveniles to mature males to females during ontogeny (Lalli and Wells, 1978). Their lifespans are thought to be between 0.5 and 2 years (Gannefors et al, 2005;Hunt et al, 2008;Kobayashi, 1974;Wang et al, 2017;Wells, 1976a). Isotopic studies have found that pteropods calcify between 50 and 650 m depth (Fabry and Deuser, 1992;Juranek et al, 2003;Keul et al, 2017), suggesting they are exposed to a wide range of water chemistries during their diurnal migration.…”
Section: Understanding Natural Pteropod Variabilitymentioning
confidence: 99%
“…Although net catches have the advantage of sampling pteropod populations at the time of collection, they only represent a snapshot in time. Pteropods have patchy distributions (Bednaršek et al, 2012a;Thibodeau and Steinberg, 2018;Wang et al, 2017), and therefore pteropod yields in net samples are highly variable. Sediment traps use a large, upward-facing cone to collect the flux of organic and inorganic particles that sink through the water column into collection cups containing preservative.…”
Section: Understanding Natural Pteropod Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Pteropods are protandric hermaphrodites, meaning they transition from juveniles, to mature males, to females during ontogeny (Lalli and Wells, 1978). Their lifespans are thought to be between 0.5 and 2 years (Gannefors et al, 2005;Hunt et al, 2008;Kobayashi, 1974;Wang et al, 2017;Wells, 1976a). Isotopic studies have found that pteropods calcify between 50 and 650 m depth (Fabry and Deuser, 1992;Juranek et al, 2003;Keul et al, 2017) suggesting that they are exposed to a wide range of water chemistries as they migrate through the water column diurnally.…”
Section: Understanding Natural Pteropod Variabilitymentioning
confidence: 99%
“…Although net catches have the advantage of sampling pteropod populations at the time of collection, they only represent a snapshot in time. Pteropods have patchy distributions (Bednaršek et al, 2012a;Thibodeau and Steinberg, 2018;Wang et al, 2017), and therefore pteropod yields in net samples are highly variable. Sediment traps use a large, upward facing cone to collect the flux of organic and inorganic particles that sink though the water column into collection cups containing preservative.…”
Section: Understanding Natural Pteropod Variabilitymentioning
confidence: 99%